Evidence for ultra-cold traps and surface water ice in the lunar south polar crater Amundsen - Sefton-Nash, E; Williams, J-P; Greenhagen, BT; Warren, TJ; Bandfield, JL; Aye, K-M; Leader, F; Siegler, MA; Hayne, PO; Bowles, N; Paige, DA (Elsevier, 2019)
The northern floor and wall of Amundsen crater, near the lunar south pole, is a permanently shaded region (PSR). Previous study of this area using data from the Lunar Orbiter Laser Altimeter (LOLA), Diviner and LAMP instruments aboard Lunar Reconnaissance Orbiter (LRO) shows a spatial correlation between brighter 1064 nm albedo, annual maximum surface temperatures low enough to enable persistence of surface water ice (<110 K), and anomalous ultraviolet radiation. We present results using data from Diviner that quantify the differential emissivities observed in the far-IR (near the Planck peak for PSR-relevant temperatures) between the PSR and a nearby non-PSR target in Amundsen Crater.